Relationship Between Gestational Weight Gain and Pregnancy Complications or Delivery Outcome - Yang, Wenjia (Sci Rep, 2017)
The purpose of this study is to analyse the association between gestational weight gain and delivery outcome or the morbidity of pregnancy complications. A total of 1,102 pregnant women who delivered at Peking University People’s Hospital in China between January 2011 and December 2012 were included in this study. We divided them into 4 groups according to the baseline BMI quartiles and weight gain quartiles in different trimesters of pregnancy to analyse the status of delivery outcome and morbidity of pregnancy complications. Baseline BMI was significantly positive correlated with the morbidity of gestational hypertension and gestational diabetes. Weight gain in the second trimester of pregnancy was significantly positively correlated with the morbidity of macrosomia. Weight gain in the third trimester of pregnancy showed significantly positive correlation with the morbidity of macrosomia, and significantly negative correlation with the morbidity of neonatal death, preterm birth, gestational diabetes, and low birth-weight infant. Gestational weight gain showed significantly positive correlation with the morbidity of macrosomia and significantly negative correlation with neonatal death, stillbirth, gestational diabetes, preterm birth and low birth-weight infant. There is a correlation between baseline BMI, pregnancy weight gain and gestational complications, adverse pregnancy outcomes, and status of neonate in varying degrees.